Total synthesis of (±)-fumimycin and analogues for biological evaluation as peptide deformylase inhibitors. Issue 24 (14th June 2019) - Zaghouani, Mehdi; Bögeholz, Lena A.K.; Mercier, Evan; Wintermeyer, Wolfgang; Roche, Stéphane P.
Abstract: A concise 7-step total synthesis of (±)-fumimycin in 11.6% overall yield is reported. An acid-catalyzed intramolecular aza-Friedel–Crafts cyclization was developed to construct the benzofuranone skeleton of the natural product bearing an α, α-disubstituted amino acid moiety in a single step. Regioselective chlorination followed by a Suzuki–Miyaura cross-coupling rapidly enabled the preparation of a library of analogues which were evaluated against peptide deformylase for antibacterial activity. Graphical abstract: Image 1